Analysis of The Use of Discussion And Question And Answer Methods As an Effort to Improve Student Physics Learning Outcomes - Sapitri, Delia; Siti Indriyati (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This study aims to find out how the views of teachers and students regarding the use of discussion and question-and-answer methods in learning physics as an effort to improve student learning outcomes, especially in the wave material on class XI MIA students at Madrasah Aliyah Negeri 2 Muaro Jambi for the 2022/2023 academic year. The population in this study were students of class XI MIA with a total of 22 students, with 11 male students and 11 female students. Sampling in research This method uses total sampling, where the entire population is used as a sample. Data was collected through observation through a questionnaire containing items, questions, and teacher interviews. Research results show that the views of teachers and students on how to use the discussion and question method answer in physics subjects are categorized quite well. The average students say that this method is suitable for use in physics lessons but still hesitates to say that using this method of discussion and question and answer can help them better understand the material. Still, the students also do not think negatively about the method. This, too, was put forward by the physics subject teacher at the school; he said that the use of discussion and question-and-answer methods is quite good and effective.